“Why Are You Running Away From Social Media?” Analysis of the Factors Influencing Social Media Fatigue: An Empirical Data Study Based on Chinese Youth - He, jianping; Liu, Yixuan (Frontiers in Psychology, 2021)
With the digital era, social media is increasingly permeating people's fragmented lives. While enjoying the convenience and speed of online socializing, people are gradually surrounded by a variety of information. Through observations and interviews, we found that young people are plagued by negative comparisons, interaction dysfunction, information overload, social overload, and intergenerational communication in the process of participating in social media, and more and more young people feel overwhelmed in the process of online socialization, and the phenomenon of social media fatigue gradually spreads. This paper combines the existing relevant theoretical models of the influencing factors of social media fatigue and the real-life empirical materials of youth groups, enriches into new research variables, and validates the data of relevant variables through a questionnaire survey (n=663), so as to explore the influencing factors of social media fatigue of youth groups and inductively analyze the inner logic of the emergence of social media fatigue of youth groups. It was found that negative comparison, interaction dysregulation, information overload, social overload, self-efficacy, and impression management all had significant positive effects on social media fatigue behaviors; privacy anxiety and intergenerational communication had no significant positive effects on social media fatigue behaviors.